El riesgo de mercado y la rentabilidad de las cooperativas de ahorro y crédito del segmento 2 de la provincia de Chimborazo periodo 2021 - Galora Calles, Dennys Paul (2024)
ABSTRACT: Market risk and profitability are fundamental aspects that every financial institution must consider to ensure stability and growth. Savings and credit cooperatives are no exception, as they must navigate various economic and financial variables that can impact their performance. This study aims to analyze the impact of market risk on the profitability of savings and credit cooperatives in segment 2 in the province of Chimborazo during 2021. Both quantitative and qualitative approaches were used, employing a non-experimental design at a descriptive and correlational level, with documentary and field research. The analysis focused on three entities registered with the Superintendency of Popular and Solidarity Economy: 4 de Octubre, Lucha Campesina, and Educadores de Chimborazo Ltda. Surveys were conducted with 30 financial area workers, and an analysis of market risk and profitability was performed. The results indicate a downward trend in profitability levels for 2021, which may be linked to changes in the interest rates offered to their members, the profitability of their operations, and the demand for credit by associates. It was concluded that the primary market risks affecting these cooperatives are high volatility in interest rates, political and economic uncertainty, and the ongoing impact of the COVID-19 pandemic. The study determined that market risk significantly affects the profitability of savings and credit cooperatives in segment 2 of the province of Chimborazo. Keywords: Savings and credit cooperatives, Market risk, Profitability, Value at Risk.